The education of Dixie Dupree - Everhart, Donna (New York, NY : Kensington Books, 2016)
In 1969 Alabama, eleven-year-old Dixie Dupree's habit of lying leaves her in trouble when her father unexpectedly departs and she finds herself in desperate need of help.
Keywords: Mothers and daughters -- Fiction; Child abuse -- Fiction; Dysfunctional families -- Fiction; Mother-daughter relationship -- Fiction; Child abuse -- Fiction; Family life -- Fiction; Alabama -- Fiction; Alabama -- Fiction; Domestic fiction; Historical fiction; Coming of age fiction; Historical fiction